DIALECTS AT THE BORDER BETWEEN KOREA AND CHINA - LEE, Choonkyu (International Journal of Korean Humanities and Social Sciences, 2016)
In this paper, we seek a closer comparative dialectological study of the dialects of the Democratic People’s Republic of Korea and the Korean dialects of the ethnically Korean Chinese near the Korea-China border. Accessible resources published in English and other languages besides Korean are particularly necessary in these times of increasing instability in the North Korean regime and foreseeable cases of asylum seekers. Speech samples are discussed to illustrate the relative difficulty of distinguishing between North Korean and Korean-Chinese speakers, compared to distinguishing between North Korean and South Korean speakers. Based on an over-view of previous literature, some guidelines are developed for identifying some distinguishing characteristics of these speech communities. Continuing dialectological research with refugees and field research making direct comparisons between these communities are necessary for further and up-to-date insight.